STUDENT ENTERPRENEURSHIP: MOTIVATION AND CHALLENGES - Dorothea Ririn Indriastuti, Saiful Bahri, Yustina Wuri Wulandari, (PROCEEDING INTERNASIONAL SEMINAR, 2015)
In an effort for Universitas of Slamet Riyadi (UNISRI) mission is to provide education, to the spirit of entrepreneurship, the development of entrepreneurship for students will be developed within the University of Slamet Riyadi. To create an independent entrepreneur based accordance with the field of science and technology, mentoring and entrepreneurial training activities for students must be done with planning and commitment. Therefore, through the implementation of The Grant Program for Entrepreneurship based Science and Technology of the University of Slamet Riyadi (Iptek bagi Kewirausahaan âIbKâ UNISRI) has the goal of creating new entrepreneurial independent, professional and business ethics-based science and technology in accordance with the study of scientific fields, improving business management skills for students, and create entrepreneurial training methods that are appropriate for students or graduates so that they can develop themselves in industrial societies.Methods for achieving the objectives and specific targets include entrepreneurship training, and practice in the field or internships, as well as study visits. Entrepreneurial training conducted by resource persons on a scheduled basis according to their expertise, whether originating from inside or outside the UNISRI. This training is intended to provide knowledge of entrepreneurship, encourage the growth of entrepreneurship motivation, increase understanding of management in the organization, production, finance or marketing, creating a business plan or feasibility study, and provides an understanding of business ethics for students. While apprenticeship implemented to give practical experience of entrepreneurship to students through the daily work involved in a business unit. In addition to students who have begun or alumni who are interested in entrepreneurship or new alumni pioneering efforts, it will further improve the entrepreneurial activity that has been previously occupied.Based on the objectives, specific targets for entrepreneurial science and technology program for students Unisri can produce independent entrepreneurs and science and technology-based professional and business ethics and young entrepreneurs who are ready to move in society. It also produces a more diverse business cluster with the products or services produced by the students have the advantage of science and technology and be able to compete, the business cluster food (fruit juice, a variety of snacks), services (computer, photography, rental ornamental.The activity of IbK UNISRI that have been implemented in 2014, the results can be summarized as follows: the necessary business who genuinely requires careful planning through a blend of academic and student activities at universities, recruitment of tenants (participants) takes techniques and strategies, tenant assistance should always be done in a sustainable manner, the tenant must be motivated by examples of real entrepreneurs, and tenants need to be given incentives venture capital and technology as a trigger to immediately take actions in self-employment.Keywords: student entrepreneurship, independence, professionalism, and ethical entrepreneurship